On-chip near 100 dB pump filtering using silicon ion implantation - Varri, Akhil; Wendland, Daniel; Pradip, Ravi; Taherinia, Shabnam; Zhao, Zhe; Lomonte, Emma; Lenzini, Francesco; Brückerhoff-Plückelmann, Frank; Pernice, Wolfram (Optics express, 2025)
Integrated photonics is an exciting platform for quantum communication, computing, and sensing due to its inherent stability and scalability. However, full monolithic or hybrid photonic quantum technology demonstrations remain limited owing to performance and integration challenges. One of the main challenges is the filtering the high-power classical pump light from the generated photons in spontaneous parametric down-conversion sources. Here, we report what we believe to be a novel optical filtering technique based on silicon ion implantation in silicon nitride (SiN) waveguides. Our approach effectively introduces selective absorption of near-visible light, achieving nearly 100 dB suppression of the pump light at 775 nm. On the contrary, the insertion loss for light in the telecom C-band near 1550 nm is just around 4 dB with a scope of significant reduction. This result paves the way for practical and efficient integration of quantum sources, filters, and detectors on-chip, advancing the field toward scalable quantum photonic systems.